Development of a Glycocluster Adjuvant Mimicking Natural Yeast beta-(1,2)-Structures - Mäkinen, Kaarina (Annales Universitatis Turkuensis D 1148, 2015)
Allergy is characterized by T helper (Th) 2-type immune response after encounter with an allergen leading to subsequent immunoglobulin (Ig) E-mediated hypersensitivity reaction and further allergic inflammation. Allergen-specific immunotherapy (SIT) balances the Th2-biased immunity towards Th1 and T regulatory responses. Adjuvants are used in allergen preparations to intensify and modify SIT. β-(1,2)-oligomannoside constituents present in Candida albicans (C. albicans) cell wall possess Th1-type immunostimulatory properties. The aim of this thesis was to develop a β-(1,2)-linked carbohydrate compound with known structure and anti-allergic properties to be applied as an adjuvant in SIT. First the immunostimulatory properties of various fungal extracts were studied. C. albicans appeared to be the most promising Th1-inducing extract, which led to the synthesis of various mono- or divalent oligomannosides designed on the basis of C. albicans. These carbohydrates did not induce strong cytokine production in human peripheral blood mononuclear cell (PBMC) cultures. In contrast to earlier reports using native oligosaccharides from C. albicans, synthetic -(1,2)-linked mannotetraose did not induce any tumor necrosis factor production in murine macrophages. Next, similarities with synthesized divalent mannosides and the antigenic epitopes of β-(1,2)-linked C. albicans mannan were investigated. Two divalent compounds inhibited specific IgG antibodies binding to below 3 kDa hydrolyzed mannan down to the level of 30–50% showing similar antigenicity to C. albicans. Immunomodulatory properties of synthesized carbohydrate assemblies ranging from mono- to pentavalent were evaluated. A trivalent acetylated dimannose (TADM) induced interleukin-10 (IL-10) and interferon-γ responses. TADM also suppressed birch pollen induced IL-4 and IL-5 responses in allergen (Bet v) stimulated PBMCs of birch pollen allergic subjects. This suppression was stronger with TADM than with other used adjuvants, immunostimulatory oligonucleotides and monophosphoryl lipid A. In a murine model of asthma, the allergen induced inflammatory responses could also be suppressed by TADM on cytokine and antibody levels.